A theory of multiple photon absorption by graphene in intense laser fields. Issue 1 (10th December 2012) - Faisal, Farhad H. M.; Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
<x xml:space="preserve">Abstract</x> A theoretical analysis of multiple photon absorption by Dirac fermions in graphene subjected to intense laser fields is made. An analytic expression for the probability of n‐photon absorption is derived. It shows that the fundamental functional dependence of n photon absorption rate is governed by a Bessel function of order n, <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbp52s" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Jn(gcos(ϕp−θ0)), where <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbp583" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />g=2vFeFℏω2, <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbp55f" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />vF is the Fermi‐velocity, F is the peak field strength, ω is the frequency; <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbp4sv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ϕp and θ0 are the polar angles of the fermion momentum and the laser polarization, respectively. The result is used to investigate the rate of n photon absorption in the THz and the near‐infrared domains and both in the weak‐field perturbative, and the strong‐field non‐perturbative intensity regimes. Formation of an n‐photon absorption plateau followed by an exponential cut‐off beyond <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg1tsbp4m3" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />n=ncut−off≈g is also predicted to occur.